Bioactive compounds from Zanthoxylum acanthopodium phyllosphere bacteria with antifungal potential against Candida albicans - ENNY NUGRAHENI; DEBIE RIZQOH; LIYA AGUSTIN UMAR; SIPRIYADI SIPRIYADI; AZELLA CHIKA FAUZIA; SHELLA SHARON (Society for Indonesian Biodiversity, 2026)
Abstract. Nugraheni E, Rizqoh D, Umar LA, Sipriyadi, Fauzia AC, Sharon S. 2026. Bioactive compounds from Zanthoxylum acanthopodium phyllosphere bacteria with antifungal potential against Candida albicans. Biodiversitas 27 (1): d270102. https://doi.org/10.13057/biodiv/d270102. Zanthoxylum acanthopodium (andaliman), an endemic Rutaceae species from Samosir Island, Indonesia, with high economic and medicinal value, harbors phyllosphere bacteria that may produce antifungal metabolites. However, their bioactive compounds remain poorly characterized. This study aimed to identify bioactive compounds from the phyllosphere bacteria of Z. acanthopodium and to evaluate their antifungal potential against Candida albicans. Phyllosphere bacterial isolates were collected and evaluated against C. albicans grown in Potato Dextrose Broth (PDB) using a dilution assay to determine the minimum inhibitory concentration (MIC), and the ethyl acetate extracts were subsequently analyzed by GC-MS to identify constituent compounds. MIC assays showed that the crude extract inhibited C. albicans in all isolates at 100% concentration. Molecular identification based on 16S rRNA revealed these isolates as Brevundimonas sp. and Pseudomonas sp. GC-MS detected phenolic compounds, including isodiospyrin and 1-methyl-ethyl compound. Molecular docking using the C. albicans EXO-β-(1,3)-glucanase protein (PDB ID: 1EQP) demonstrated favorable binding energies (ΔG≤0), indicating spontaneous interactions. Isodiospyrin showed the strongest affinity with ΔG –8.56, while the 1-methyl-ethyl compound exhibited the best binding affinity and inhibition constant among the detected compounds. The findings confirm that phyllosphere bacteria of Z. acanthopodium exhibit antifungal activity against C. albicans. Isodiospyrin and 1-methyl-ethyl compound emerged as promising candidates for further antifungal development. Future studies should validate their efficacy through in vitro and in vivo assays, isolate specific antifungal metabolites, and optimize production for potential therapeutic applications.